PENGARUH GOOD CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS 2010-2012) - Totok Rudianto (Jurnal Telaah dan Riset Akuntansi, 2014)
ABSTRACT This research aimed to investigate the influence of composition independent commissioner,independent audit committee, institutional ownership, managerial ownership quality audit to earnings manage2010 -2012. It used 300 companies. This  research used a cencus menthod, the analysis conducted in this research was multiple  regression analysis. The result of the research show that simultaneously composition of independent commissioner, independent audit committe, institutional ownership, managerial ownership, audit quality influenced to earnings management. Meanwhile, partially only quality audit influenced to earnings management. The variable composition of independent commissioner, independent audit committe, institutional ownership and managerial ownership didnot influence to earnings management. For the following research, it is recommended to add several veariabels such as  competency  board of directors, competency board of commissioner,  and gender of board of commissioner.  Keywords: earnings management, composition independent commissioner, independent audit  committe, institutional ownership, managerial  ownership  and quality  audit.